Analisa Kesesuaian Pengelolaan Sampah di TPA Jatibarang Semarang oleh DLH Kota Terhadap Kewajiban Hukum Berdasarkan Berdasarkan Peraturan Daerah Kota Semarang Nomor 6 Tahun 2012 tentang Pengelolaan Sampah - Ranita ivana (CV Rewang Rencang, 2024)
With the increasing population and consumption activities, Semarang City generates approximately 1,110–1,200 tons of waste daily, all disposed at the Jatibarang Final Processing Site (TPA). This study employs an empirical juridical approach using qualitative methods, including interviews with the Environmental Agency (DLH) and field observations. Findings show that DLH’s waste management practices do not fully comply with Regional Regulation No. 6/2012, particularly Article 22 on final-stage principles. Due to budget constraints, controlled landfill is used instead of sanitary landfill. Despite efforts in public education, infrastructure development, and green technology planning (PSEL), systemic improvements and broader community participation remain essential.